REDUCED VOCABULARY IN MODERN RUSSIAN POLITICAL DISCOURSE - Aslbek Ergashev (Galaxy International Interdisciplinary Research Journal, 2024)
The article describes the features of the functioning of reduced vocabulary in political discourse.